Kejahatan yang Banal dan Kekerasan oleh Negara: Refleksi Hannah Arendt atas Pengadilan Adolf Eichmann di Yerusalem - Jena, Yeremias (Jurnal Etika Respons, 2009)
Following the whole process of the trial of Eichmann in Jerusalem, Hannah Arendt realised that crimes and violence (evil) done by Eichmann and the Nazi were the clues of the absence of the thoughtfulness. The question arises as to why a thoughtless man like Eichmann did such a big crime and violence against the Jews? The absence of reflective and philosophical thoughts that expels a moral agent to justify his moral deeds has become the root cause why Eichmann failed to act according to some fundamental moral principles. The trial of Eichmann was really an exposure of the banality of evil against humanity. Could reason or reflective thoughts hinder a moral agent from evil deeds? How should we understand the banality of evil in political exercise? By reflecting the thoughts of Hannah Arendt on the banality of evil, this article discusses and tries to answer these questions.